Изменения в ихтиофауне низовьев Днепра и Днепровско-Бугского лимана в связи с гидростроительством - Залуми, С.Г. (Вестник зоологии, 1967)
The construction of the cascade of reservoirs in the middle and low Dnieper and decrease of the river discharge change the hydrological regime of the low Dnieper and the Dnieper-Bug estuary: the floods are rare now, flow speed falls, the estuary becomes salty. Sea species of fish, which were not observed previously, appeared now: Odontogadus merlangus euxinus, Mugil saliens, Crenilabrus occelatus; the number of salt water fishes — Clupeonella delicatula delicatula, Atherina rnochon pontica, Gobiidae — increased. Atherina mochon pontica penetrated into the Dnieper and began to propagate now, that was not observed previously. The rheophilic species — Cliondrostoma nasus natio boristhe-nicum, Leuciscus leuciscus, Gobio gobio, Abrarnis ballerus and Abramis saga disappeared from the ichthyofauna of the low Dnieper. Such species as Leuciscus cephalus, Aspius aspius, Leuciscus idus are oppressed; Palecus cultratus lost its industrial value. Propagation of the Acipenser guldenstadti colchicus and Alosa vissleri politica is impeded and of small effect. The isolation of the low Dnieper and the Dnieper-Bug estuary from the sea is proposed by means of dam construction in Ochakov region.